2009
DOI: 10.1186/1471-2407-9-115
|View full text |Cite
|
Sign up to set email alerts
|

CYP17, GSTP1, PON1 and GLO1gene polymorphisms as risk factors for breast cancer: an Italian case-control study

Abstract: BackgroundEstrogens, environmental chemicals with carcinogenic potential, as well as oxidative and carbonyl stresses play a very important role in breast cancer (BC) genesis and progression. Therefore, polymorphisms of genes encoding enzymes involved in estrogen biosynthesis pathway and in the metabolic activation of pro-carcinogens to genotoxic intermediates, such as cytochrome P450C17α (CYP17), endogenous free-radical scavenging systems, such as glutathione S-transferase (GSTP1) and paraoxonase 1 (PON1), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
65
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 38 publications
15
65
2
Order By: Relevance
“…First is the substitution mutation in codon 105 of exon 5, which causes substitution of the isoleucine with valine at nucleotide position 313 (A to G transition) 31 with the mutant genotype (containing valine allele) effecting the enzyme activity as well as specificity. 19 This observation has been confirmed by the number of published studies concerning the role of this single-nucleotide polymorphism in relation to the individuals' susceptibility to the various diseases 32 including many cancers, mainly breast cancer, 24,25,[33][34][35] bladder cancer, testicular cancer, and prostate cancer. [36][37][38] The epigenetic silencing of this gene in the form of CpG hypermethylation is the second mechanism involved in the cancer progression.…”
Section: Discussionsupporting
confidence: 61%
“…First is the substitution mutation in codon 105 of exon 5, which causes substitution of the isoleucine with valine at nucleotide position 313 (A to G transition) 31 with the mutant genotype (containing valine allele) effecting the enzyme activity as well as specificity. 19 This observation has been confirmed by the number of published studies concerning the role of this single-nucleotide polymorphism in relation to the individuals' susceptibility to the various diseases 32 including many cancers, mainly breast cancer, 24,25,[33][34][35] bladder cancer, testicular cancer, and prostate cancer. [36][37][38] The epigenetic silencing of this gene in the form of CpG hypermethylation is the second mechanism involved in the cancer progression.…”
Section: Discussionsupporting
confidence: 61%
“…We studied the Glu111Ala polymorphism of glyoxalase I in patients with breast cancer 36 and were able to show that the higher frequency of the mutated C allele was found in patients with negative estrogen receptors and in patients and more advanced disease (clinical stage III) compared to controls (P < 0.05) suggesting that the presence of the C allele could be a negative prognostic factor in breast cancer. In a large Italian study of patients with breast cancer cancer 37 polymorphism of glyoxalase I was associated with breast cancer in univariate analysis but a number of confounding factors obfuscate the results. In another large study in Malaysian patients with breast cancer 38 the genotype and allele frequencies of Ala111Glu glyoxalase I polymorphism were not significantly different for patients and controls.…”
Section: Ages Their Metabolism and Cancermentioning
confidence: 99%
“…Accordingly PON1 L55M polymorphism was associated with an increased risk of developing childhood leukemia (LM + MM, OR 1.93, 95%CI 1.32-2.81). 34 Moreover, some researchers observed an increased risk associated with the MM genotype for breast [30][31][32] , and prostate cancer. 33 Similarly, within the meta-analysis of 21 case-control studies involving 5.627 cases and 6.390 controls, it was observed that PON1 L55M polymorphism was associated with an increased risk for breast, prostate, and ovarian cancer.…”
Section: Resultsmentioning
confidence: 99%